Self-tuning Controllers for a Coupled Tank Pilot Plant: Evaluation and Comparison - Ab Ghani, Mohd Ruddin (1993)
Real-time self tuning control was implemented on a coupled tank pilot plant using a microcomputer. Three different algorithms namely, generalized minimum variance, pole placement and extended horizon were used. The performances of these controllers are evaluated for set-point tracking experiments and load disturbance experiments.